Epidemiology of Stemphylium Blight of Lentil - Huq, M Ihsanul; Khan, AZM Nowsher Ali (Bangladesh Journal of Scientific and Industrial Research, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Among the atmospheric factors maximum and minimum temperature, relative humidity ranging from 20.5-29.0°C (mean 23.7°C), 5.4-13.3°C (mean 14.2°C) and 78.0-84.5% (mean 81.0%), 48.0-63.0% (mean 55.5%) respectively are the predisposing factors for disease initiation. Whereas the maximum and minimum temperature, relative humidity ranging from 20.5-35.0°C and 13.0-21.0°C, 78.0 - 100.0% and 48.0-80.2% respectively and rainfall 1.2-14.6mm are favorable for disease development. The trends of disease development among the sowing dates were similar. The lowest and the highest severity were noted on November 01 and December 30 respectively. Key words: Epidemiology, Stemphylium blight, Lentil and Meteorological factor. doi: 10.3329/bjsir.v43i4.2241 Bangladesh J. Sci. Ind. Res. 43(4), 513-520, 2008